2018
DOI: 10.1001/jamapediatrics.2018.1508
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Heritability of Child Body Mass Index by Obesogenic Home Environment

Abstract: This cohort study investigates the association between obesogenic home environment and heritability of body mass index among children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 65 publications
2
86
0
1
Order By: Relevance
“…This is a rapidly expanding and diverse body of knowledge with a number of subfields. One area of research pertains to genetic factors in relation to BMI or obesity per se . For example, in a review of research on twins reared apart, approximately two‐thirds of the variability in BMI was attributed to genetic factors .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is a rapidly expanding and diverse body of knowledge with a number of subfields. One area of research pertains to genetic factors in relation to BMI or obesity per se . For example, in a review of research on twins reared apart, approximately two‐thirds of the variability in BMI was attributed to genetic factors .…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a review of research on twins reared apart, approximately two‐thirds of the variability in BMI was attributed to genetic factors . However, genetic contributions to obesity could vary with age and have a greater influence during childhood than in adulthood and differ according to the degree to which the home environment is obesogenic . As an example of mechanisms, Belsky et al identified that genetic risk for obesity partly operated through accelerated weight gain in the early years after birth …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus it is critical to understand how gene-by-environment interactions are contributing to metabolic dysfunction. Such interactions have been shown to underlie variation in obesity and diabetes risk [38], and many individual genes have been identified with natural variants in human populations affecting metabolic response to environmental perturbations [914]. Research in animal models, in particular mouse models, has been used to manipulate dietary intake and environment in order to better understand the gene-by-environment interactions most relevant to human metabolism [1519].…”
Section: Introductionmentioning
confidence: 99%